Effect of fibroblast growth factor and enamel matrix derivative treatment on root resorption after delayed replantation. Issue 1 (7th October 2014) - Tuna, Elif Bahar; Arai, Kiyoshi; Tekkesin, Merva Soluk; Seymen, Figen; Gencay, Koray; Kuboyama, Noboru; Maeda, Takahide
Abstract Background Periodontal ligament (PDL) healing and long term prognosis of replanted avulsed teeth should rely on several factors including length of extra‐oral dry time and type of the storage medium. The status of periodontal ligament is critical for the healing of replanted teeth. Different substances have been used for root surface treatment to promote formation of PDL and increase the survival of avulsed teeth submitted to replantation. Aim The purpose of this study was to assess the effect of recombinant basic fibroblast growth factor 2 (bFGF) and enamel matrix derivative (EMD) on root resorption after delayed replantation. Design 18 freshly extracted single‐rooted incisor and premolar teeth were extracted from the beagle dogs and immersed in whole bovine milk for 45 and 60 min (n = 3 each). Following storage period, sockets washed and teeth were treated with bFGF and EMD and replanted into the sockets. After 8 weeks, dogs were sacrificed, specimens processed to 4‐μm thick serial sections for histopathologic examination and morphometric assessments. Thus, the proportions of the roots that exhibited signs of surface resorption, inflammatory resorption, and replacement resorption, that is, ankylosis and normal PDL were noted. Results The percentage of root resorption was in the following order: EMD>milk>bFGF for 45 min and milk>EMD>bFGF for 60 min. For all groups, teeth stored 60 min showed significantly higher incidence of PDL resorption than those stored for 45 min (P < 0.01). The highest incidence of replacement resorption was observed in teeth treated with EMD for 60 min. After 8 weeks, the least resorption was found in bFGF‐treated group (P < 0.01). Conclusions The findings of this study suggest that use of bFGF favored the formation of new periodontal ligament; prevent ankylosis and resorption process following delayed replantation of teeth while EMD shows replacement resorption, which may turn to ankylosis.